Fixation of Unstable Osteochondritis Dissecans Lesions and Displaced Osteochondral Fragments Using New Biodegradable Magnesium Pins in Adolescents. (December 2021) - Jungesblut, Oliver D.; Moritz, Menard; Spiro, Alexander S.; Stuecker, Ralf; Rupprecht, Martin
Objective: Fixation of unstable osteochondritis dissecans (OCD) lesions and displaced osteochondral fragments are frequently performed procedures in pediatric orthopedic surgery. Since 2018, CE-certified MAGNEZIX pins are used in our institution in these cases. The aim of this study was (1) to analyze safety, efficiency, and limitations of magnesium-pin-based fixation of unstable OCD lesions and displaced osteochondral fragments and (2) to report clinical and radiological outcomes at short-term follow-up (FU). Design: In this prospective cohort study, 19 patients (10 girls and 9 boys) were included. Inclusion criteria were (1) magnetic resonance imaging–confirmed unstable OCD lesion or displaced osteochondral fragment, (2) fixation with magnesium-based pins, and (3) minimum FU of 6 months. X-rays were taken 6 weeks and 6 months after operation and magnetic resonance imaging scans every 4 to 6 months to assess the healing progress. Results: In total 67 pins were used, with a mean of 3.6 ± 1.4 per patient. Average age at surgery was 13.7 years (11-17 years). Mean time of operation was 56 ± 31 minutes, including arthroscopy, fixation, and patellar realignment ( n = 6). No intraoperative complications occurred. Average FU was 11.3 ± 4.2 months (6-20 months). No redislocation or new dislocation occurred. Until now a complete radiographic healing occurred in 12 cases. Due to an implant failure in one case 11 weeks after the index surgery a revision became necessary. Conclusions: In short-term FU of 11 ± 4 months MAGNEZIX pins provide high stability after fixation of unstable OCDs and displaced osteochondral fragments leading to uncomplicated and timely healing.